The evaluation of glutamine supplementation into the diet on the growth performance, intestinal structure and function of striped catfish Pangasius hypophthalmus (Sauvage, 1878) fry - Uttari Dewi; Dedi Jusadi; Mia Setiawati; Sri Nuryati (Jurnal Iktiologi Indonesia, 2022)
A triplicate experiment was conducted to evaluate the effect of glutamine supplementation in the diet on the structure and function of intestine and the growth performance of striped catfish Pangasius hypopthalmus. Forty fishes with an initial body weight of 0.82 ± 0.01 g were distributed into a rectangular aquarium with a size of 60×50×40 cm and a water volume of 70 L. Fish were fed on the diet supplemented with glutamine of either 0, 1, 2, or 3%, respectively. Fish were fed on the diet at satiation for 60 days. Results showed that fish fed on the diet supplemented with 1, and 2% of glutamine significantly had the highest growth performance, including specific growth rate, protein retention, and feed efficiency. On the other hand, feeding on a diet supplemented with 3% of glutamine did not significantly affect the growth performance of fish. Fish in 1% and 2% glutamine treatments had better structure and function of intestine than two other groups of fish, namely the ratio of intestine length with body length, villus surface area, and protease enzyme activity. Thus, supplementation of 1% and 2% glutamine in the diet improves the structure and function of intestine and the growth performance of striped catfish. Abstrak Percobaan dilakukan untuk mengevaluasi pengaruh penambahan glutamin pada pakan terhadap struktur dan fungsi usus, serta kinerja pertumbuhan ikan patin Pangasius hypopthalmus. Ikan uji yang digunakan sebanyak 40 ekor dengan bobot awal 0,82 ± 0,01 g dipelihara dalam akuarium berukuran 60 × 50 × 40 cm dan volume air 70 L. Ikan diberi pakan uji dengan penambahan glutamin 0, 1, 2, dan 3%. Ikan diberi pakan uji secara at satiation selama 60 hari. Hasil penelitian menunjukkan bahwa ikan yang diberi pakan dengan penambahan glutamin 1% dan 2% secara signifikan menghasilkan kinerja pertumbuhan tertinggi, termasuk laju pertumbuhan spesifik, retensi protein, dan efisiensi pakan. Di sisi lain, pakan yang ditambah dengan glutamin 3% tidak signifikan memengaruhi kinerja pertumbuhan ikan. Ikan uji pada perlakuan glutamin 1% dan 2% menghasilkan struktur dan fungsi usus yang lebih baik dibanding perlakuan lainnya, yakni rasio panjang usus dengan panjang tubuh, luas permukaan vili dan aktivitas enzim protease. Disimpulkan bahwa penambahan glutamin 1% dan 2% pada pakan meningkatkan struktur dan fungsi usus serta kinerja pertumbuhan benih ikan patin.